Predicting risk of dyslexia with an online gamified test - Baeza Yates, Ricardo; Ali, Abdullah; Bigham, Jeffrey; Serra, Miquel; Rello, Luz (Public Library of Science, 2020)
Dyslexia is a specific learning disorder related to school failure. Detection is both crucial and challenging,especially in languages with transparent orthographies,such as Spanish. To make detecting dyslexia easier,we designed an online gamified test and a predictive machine learning model. In a study with more than 3,600 participants,our model correctly detected over 80% of the participants with dyslexia. To check the robustness of the method we tested our method using a new data set with over 1,300 participants with age customized tests in a different environment -a tablet instead of a desktop computer- reaching a recall of over 78% for the class with dyslexia for children 12 years old or older. Our work shows that dyslexia can be screened using a machine learning approach. An online screening tool in Spanish based on our methods has already been used by more than 200,000 people. © 2020 Rello et al. This is an open access article distributed under the terms of the Creative Commons Attribution License,which permits unrestricted use,distribution,and reproduction in any medium,provided the original author and source are credited.
Keywords: adolescent; child; controlled clinical trial; controlled study; dyslexia; female; human; machine learning; major clinical study; male; mass screening; online system; prediction; risk assessment; risk factor; attention; dyslexia; language; neuropsychological test; pathophysiology; phonetics; physiology; reading; semantics; short term memory; video game; vision; Adolescent; Attention; Child; Dyslexia; Female; Humans; Language; Machine Learning; Male; Memory; Short-Term; Neuropsychological Tests; Phonetics; Reading; Risk Factors; Semantics; Video Games; Vision; Ocular; 58 Pedagogía::5801 Teoría y métodos educativos::5801.05 Pedagogía experimental; ODS 4 - Educación de calidad